Doing Counselling Psychology the Heideggerian Way (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
In this paper I briefly explore the possibility of an existential approach to counselling psychology from a Heideggerian perspective. A brief overview of this philosopher's work is presented and a small selection of relevant themes are considered. The article concludes with the consideration that I believe Heidegger's phenomenological method might prove to be a valid starting point for a therapeutic counselling method which aims towards an understanding of what it means to be a human being, existing with others in the world.
Keywords: Heidegger; phenomenological method; ontological; ontic; Dasein; inauthentic; authentic.